1985
DOI: 10.1093/nar/13.6.2171
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of members of a family of repetitive sequences in the goat βglobin locus

Abstract: We have characterized a family of repetitive DNA elements in the beta-globin locus of the goat. These sequences are structurally analogous to the Alu families of repeats of other mammals. Repetitive elements are located both in the intervening sequences and in the intergenic regions of the goat beta-globin locus. Nucleotide sequence analysis of five repetitive elements located within the large intervening sequence of the beta-like globin genes, and four repeats located 5' to the major developmentally regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…1, the bovine genome contains three different kinds of dispersed repeat, namely, Bov-A2, Bov-tA, and Bov-B (using the nomenclature of Lenstra et al 1993). Bov-A represents the 115-bp A unit (Weiner et al 1986), which has also been designated BCS (Spence et al 1985) and BMF (Zelnick et al 1987). Bov-A2 is a homodimer of Bov-A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1, the bovine genome contains three different kinds of dispersed repeat, namely, Bov-A2, Bov-tA, and Bov-B (using the nomenclature of Lenstra et al 1993). Bov-A represents the 115-bp A unit (Weiner et al 1986), which has also been designated BCS (Spence et al 1985) and BMF (Zelnick et al 1987). Bov-A2 is a homodimer of Bov-A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…repeats and the typical SINEs indicate that the f6rmer should be placed in a separate class of repetitive elements. Other investigators have reported non-Atu types of short interspersed repeats (21)(22)(23). Some of these are apparently retrotransposons and are inserted (22).…”
Section: Mouse Myoglobinmentioning
confidence: 95%
“…Other investigators have reported non-Atu types of short interspersed repeats (21)(22)(23). Some of these are apparently retrotransposons and are inserted (22). Another group of interspersed repeats is composed of tandem repetitions of short oligonucleotides, which are highly conserved (3,24,25).…”
Section: Mouse Myoglobinmentioning
confidence: 99%
“…Contributing to this is the presence of a Nlu repeat at positions 2228-2307. This copy of the repeat shows 73% similarity to a sequence from the goat P-globin locus, in which the NZu repeat was first identified (Spence et al, 1985). This repeat is not present at this position in bovine BLG; however, a sequence with 84% sequence similarity is found at positions 6474-6553 in the 3' flanking region of ovine BLG (Harris et al, 1988).…”
Section: Comparison Of Bovine Blg and Y/-blg Y-blg Is Locatedmentioning
confidence: 71%